Penggunaan Media Audio Visual untuk Meningkatkan Hasil Belajar Siswa pada Materi Sistem Peredaran Darah Manusia di Kelas V SDN Mojorejo 01 Kota Batu - Ramadhani, Laili Alfiah; Sugiarti, Sugiarti; Rahmadina, Prilia (Jurnal Simki Pedagogia, 2023)
The purpose of this study was to determine the use of audio-visual media to improve student learning outcomes in the subject of the human circulatory system in class V SDN Mojorejo 01 Batu. The research method used was classroom action research with a total of 22 students who came from fifth grade students at SDM Mojorejo 01 Batu. The research was conducted for 1 month as many as 6 face-to-face meetings. Data collection methods used were observation, interviews and tests to measure students' cognitive learning outcomes using Essay tests, affective and psychomotor domains using observation. Processing data using descriptive analysis. The percentage gain in pre-cycle learning activities was 13.6% and the percentage gain in student learning completeness in the first cycle learning activities was 72.7%. In cycle II, student learning outcomes increased to 90.9%. the affective domain in the pre-cycle has an average value of 51%, and in the first cycle has an average of 77%, in the pre-cycle and cycle I still have not reached the expected achievement indicator of 80%. In cycle II the affective domain reached a percentage of 89%. While the psychomotor domain of students in pre-cycle is 48%, cycle I reaches 74% and cycle II reaches 89%.